A FUTURISTICS APPROACH FOR HARNESSING GREEN ENERGY: FROM POND SCUM TO POWERHOUSE ALGAE’S JOURNEY AS BIO-FUEL - Shiwangi Bharti1, Varsha Gupta1, Mansvi Yadav1, Deepesh Kumar Neelam1, Devki1, Ravi Kant Rahi1*, (Chelonian Research Foundation, 2024)
Bio-fuel is the fuel produced over a short period from biomass, rather than by the very slow natural processes involved in forming fossil fuels, such as oil. Bio-fuel can be produced from plants, agricultural, domestic, or industrial bio-waste. Algae is the term used for a large and diverse group of eukaryotic organisms that are photosynthetic and have chlorophyll as their primary photosynthetic pigment. Algal biomass contains a very high oil fraction and can be used for bio-fuel production. Various algal strains, Botryococcus braunii, Chlorella, Dunaliella tertiolecta, Gracilaria Pleurochrysis carterae, Sargassum, and others have been found to successfully and efficiently produce *biodiesel. Mechanism of biofuel production includes transesterification and esterification of oil with alcohol. This review mainly focuses on the various algal strains isolated from various sites that are responsible for bio-fuel production, production mechanisms, and various applications of bio-fuels. Keywords: Biomass, Fossil fuels, Photosynthetic, Chlorophyll, Biodiesel, Transesterification, Esterification